A Study to Assess the Practice of Incentive Spirometer Among Postoperative Patients at a Selected Hospital - V Beautily; M Shanthanu; D Alfred Solomon; R. Hemavathi (Wolters Kluwer Medknow Publications, 2024)
Background: The current study was aimed to assess the practice of incentive spirometer among postoperative patients at selected hospital. Material and Method: A descriptive observational study design with nonprobability purposive sampling was adopted to conduct a study among 60 postoperative patients of general surgery in patient department. Data were gathered by structured questionnaires using demographic variables and biological parameters. Confidentiality was maintained throughout the procedure. Collected data were analyzed by using descriptive and inferential statistics. Result: The results revealed that the Day 1, 27 (54%) had inadequate practice, 20 (40%) had moderately adequate practice, and 3 (6%) had adequate practice. On Day 2, 20 (40%) had adequate practice, 20 (40%) had moderately adequate practice, and 10 (20%) had inadequate practice. On Day 3, 36 (72%) had adequate practice, 8 (16%) had moderately adequate practice, and 6 (12%) had inadequate practice. The demographic variables did not shown statistically significant association with level of practice of flow-oriented incentive spirometer among the postoperative patients on Day 1, Day 2, and Day 3.